2010
DOI: 10.1021/ma101051m
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Molecular Mobility in Polymer Matrices: Synchronizing Switching Speeds of Multiple Photochromic Dyes

Abstract: We report a method that allows the facile synchronization of multiple photochromic dyes in a rigid polymer lens matrix together with large increases in their switching speeds. This was achieved by simple chromatographic fractionation of dye-poly(dimethylsiloxane) (PDMS) conjugates to provide tunable switching speeds with longer PDMS tails providing faster switching speeds and shorter tails providing slower switching with no effect on the electronic nature of the dyes. This was done for mono end-functional dye-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 27 publications
1
38
1
Order By: Relevance
“…The result is significantly increased coloration and fade‐speeds (approaching those seen in solution) achieved without compromising the mechanical properties of the host lens matrix. Of the polymers tested, including poly(ethylene glycol)5, 12, 13 and poly( n ‐butyl acrylate),9, 11 we found that conjugation of photochromic dyes to polydimethylsiloxane (PDMS) oligomers was most effective in enhancing fade speed 5–7. As well as being effective, PDMS was also very efficient with fairly short oligomers, ranging from about 6 to 25 siloxane repeat units, providing a large effect.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The result is significantly increased coloration and fade‐speeds (approaching those seen in solution) achieved without compromising the mechanical properties of the host lens matrix. Of the polymers tested, including poly(ethylene glycol)5, 12, 13 and poly( n ‐butyl acrylate),9, 11 we found that conjugation of photochromic dyes to polydimethylsiloxane (PDMS) oligomers was most effective in enhancing fade speed 5–7. As well as being effective, PDMS was also very efficient with fairly short oligomers, ranging from about 6 to 25 siloxane repeat units, providing a large effect.…”
Section: Introductionmentioning
confidence: 91%
“…We have previously reported a method by which exceptional photochromic switching performance is realized within rigid polymeric matrices 5–11. The covalent attachment of soft, low T g oligomers/polymers directly to photochromic dyes (polymer conjugation) provides a fluid and mobile local environment for relatively unhindered switching to occur.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we study 2 H ‐naphtho[1,2‐b]pyrans 5 , 12 , 13 , and especially the neat COOH‐terminated monolayer on Si(111) containing compound 13 as headgroup ( S6 ). These naphthopyrans were chosen because of their two thermally more stable colored open forms (OFs: transoid‐cis (TC) and transoid‐trans (TT)) (Figures , ) in comparison to other naphthopyrans . Moreover, for development of multistate switchable surfaces, they offer the possibility to use UV illumination, thermal relaxation and visible light‐illumination for switching events into several directions.…”
Section: Figurementioning
confidence: 99%
“…A new absorbance band centered at 467 nm appeared and reached maximum after irradiation of 260 s, which is attributed to the absorbance of open-form CzNP (Scheme 1). The extended π-conjugation and quasi-planar structures of MC forms resulted in the highly colored MC forms [32,33].…”
Section: Photochromism Of Cznp In Solutionmentioning
confidence: 99%